2022
DOI: 10.1002/admi.202201265
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Triboelectric Nanogenerator with Micro‐Rhombic Patterned PDMS for Self‐Powered Wearable Sensing

Abstract: In recent years, triboelectric nanogenerators (TENGs) have been used in energy harvesting and microsensing widely, and the performance of TENGs has been gradually improved through dielectric material surface modification strategies. Microscopic arrays mostly require expensive and tedious experimental steps to fabricate, such as micropillars, microneedles, cubes, and pyramids. Herein, a new type of triboelectric nanogenerator consisting of micro‐rhombic patterned PDMS (MR‐TENG) is proposed to enhance the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Unique signals are exhibited by different states of body parts. [31][32][33][34][35][36] The MSPS-TENG, which has been developed, possesses the advantageous characteristics of flexibility and stability, enabling the timely monitoring of human body movement.…”
Section: Resultsmentioning
confidence: 99%
“…Unique signals are exhibited by different states of body parts. [31][32][33][34][35][36] The MSPS-TENG, which has been developed, possesses the advantageous characteristics of flexibility and stability, enabling the timely monitoring of human body movement.…”
Section: Resultsmentioning
confidence: 99%
“…It has the advantages of high strength, good heat resistance, easy dyeing, anti-wrinkle nature, comfort and lightweight, and is often used to prepare W-TENGs. 65,66…”
Section: Friction Layer and Electrode Materials Of The W-tengmentioning
confidence: 99%
“…It has the advantages of high strength, good heat resistance, easy dyeing, anti-wrinkle nature, comfort and lightweight, and is oen used to prepare W-TENGs. 65,66 Considering hydrophobicity, Shen et al 67 used a cellulose acetate -polyurethane (CA-PU) nanober composite lm with amino surface modication as the positive friction layer. The I sc and V oc were 2.95 mA and 42 V when the relative humidity was as high as 90%.…”
Section: Friction Layer Materials For W-tengsmentioning
confidence: 99%
“…Based on extensive literature, we found that most works based on surface engineering are focused on increasing the surface area and enhancing the triboelectric charge density. However, the introduction of a microstructure increases the distance between the triboelectric material and the electrode, and its influence on the final output performance is still unclear. Based on this point, we design a conformal dome structure, where the electrode and triboelectric layer are conformal to the dome structure, and a nonconformal dome structure is used as a comparison to explore their influence on the output performance.…”
Section: Introductionmentioning
confidence: 99%